2021
DOI: 10.1111/ajag.13030
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of job quality in the Australian aged care workforce: A scoping review

Abstract: Objective As governments grapple with ageing populations, there is a need to understand more about the aged care workforce and how it is managed. Methods We undertook a scoping review according to the Preferred Reporting Items for Systematic reviews and Meta‐Analyses extension for Scoping Reviews (PRISMA‐ScR) guidelines. Scopus and PubMed were used to identify papers published between 2010 and 2020. We mapped the breadth and scale of the evidence base according to the QuInnE indicators of job quality. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Therefore, access to TD and availability of career paths are critical factors that influence perceived job quality (Burgess & de Ruyter, 2000) and employee retention (Wilson, Brown, & Cregan, 2008). "Training and education," the second most populated dimension of job quality (Carnemolla, Taylor, Gringart, & Adams, 2022), was perceived as necessary because it showed that employers value their employees and invest in their continuous development (Clarke, 2015).…”
Section: Job Quality and Trainingmentioning
confidence: 99%
“…Therefore, access to TD and availability of career paths are critical factors that influence perceived job quality (Burgess & de Ruyter, 2000) and employee retention (Wilson, Brown, & Cregan, 2008). "Training and education," the second most populated dimension of job quality (Carnemolla, Taylor, Gringart, & Adams, 2022), was perceived as necessary because it showed that employers value their employees and invest in their continuous development (Clarke, 2015).…”
Section: Job Quality and Trainingmentioning
confidence: 99%